PKM PAUD Holistik Integratif di Kecamatan Argomulyo Salatiga: Pengabdian - Sagala, Anita Chandra Dewi; Kusumaningtyas, Nila; Karmila, Mila; Rahmawati, Intan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
In the Argomulyo Salatiga subdistrict, early childhood education teachers in particular do not yet have the ability to design holistic integrative early childhood education programs and are not yet able to teach about health, nutrition, parenting, care, protection, and welfare for children in early childhood education units. Teachers' knowledge of holistic integrative early childhood education is very important for producing high-quality children. The solution offered is training and assistance in developing a holistic integrative PAUD program, as well as implementing education, health, nutrition, parenting, care, protection, and welfare for children in PAUD units. It is hoped that with holistic integrative PAUD training, teachers at the Argomulyo District PAUD Post will find it easier to design holistic integrative PAUD in their educational units. The Holistic Integrative PAUD training was conducted twice, both offline and online. The results of the Holistic Integrative PAUD program activities were continued and developed with more creative and interesting activities, which were part of a planned and documented cooperation system involving all elements of Holistic Integrative PAUD, namely education, health, nutrition, childcare, protection, and child welfare.